The role of government policies to enhance entrepreneurship through business - friendly environment: Implications for Peru - Revilla Donayre, Hilda Dora (2008)
This Paper presents the results of a research on formal or informal entrepreneurs conducted in Peru. The research, based on secondary data, aims at understanding the impact of Government policies to enhance the entrepreneurship in Peru by providing business-friendly environment to develop their activities in Peru. The policies include dealing with the challenges when doing business such as accessing to financing, starting business, dealing with licenses, property rights, paying taxes, trading across borders and the strategies adopted to overcome these problems. Additionally, this research aims at evaluating the degree of informality of entrepreneurs in Lima and other provinces, by collecting information on whether and why they are officially registered, have the required licenses to operate, pay taxes and comply with the regulations for their employees. Finally, this work aims at reflecting on which policies, if any, could facilitate the development of all enterprises and increase their degree of formality.